The issue of Representation in documentary Film - Bong, Margaret Chew Jen. (Universiti Malaysia Sarawak (UNIMAS), 2006)
This dissertation exammes the concept of documentary filmmaking which is based on the actuality, truth, social reality and historical reality, and also some filmmakers' perceptions, which I term them as "there is no correct definition of documentary". I had identified and analyzed the principle modes in documentary filmmaking. These include the historical aspect and the development of documentary filmmaking. Through the thesis film, I concluded that documentary filmmaking is not only adopting the forma I modes of documentary but the influencing of the selective method of the documentary filmmaker.